Anterior Lumbar Interbody Fusion (ALIF) versus Oblique Lateral Interbody Fusion (OLIF) at L5-S1: A Comparison of Two Approaches to the Lumbosacral Junction. (1st September 2019) - Xi, Zhuo; Burch, Shane; Chang, Chih-Chang; Ruan, Hui-bing; Eichler, Charles M; Mummaneni, Praveen V; Chou, Dean
Abstract: INTRODUCTION: The oblique lateral interbody fusion OLIF is an alternative anterior approach to the lumbar spine at L5-S1, and it is unknown how it compares to anterior lumbar interbody fusion ALIF. This abstract is to compare the radiographic and clinical factors of ALIF and OLIF at L5-S1 only. METHODS: A retrospective review of patients who underwent ALIF or OLIF at L5-S1 only at the University of California San Francisco (2013-2018) was performed. Data collected were demographics, cage parameters, perioperative factors, and radiographic parameters. RESULTS: A total of 58 patients were included (33 ALIF and 25 OLIF). The average surgical time was 211.94 min for ALIF and 154.86 min for OLIF ( P < .001). The average blood loss was 214 ml for ALIF and 74 ml for OLIF ( P < .001). The average day to solid food was 2.55 for ALIF and 0.8 for OLIF ( P < .001). The average cage height was 14.78 mm for ALIF and 12.9 mm ( P < .001) for OLIF. The average cage lordosis was 15.45° for ALIF and 12.68° ( P = .76) for OLIF. Average anterior L5-S1 disc height increase was 8.52 mm (ALIF) and 5.02 mm (OLIF) ( P = .018), and average posterior L5-S1 disc height increase was 3.34 mm (ALIF) and 1.30 mm (OLIF) ( P = .034). The average L5-S1 segmental lordosis increase was 6.82° for ALIF and 7.63° for OLIF ( P = .638). CONCLUSION: Patients who underwent OLIF at L5-S1 had shorter ileus duration compared to ALIF and comparable operative times and blood loss. ALIF afforded larger cages to be placed, resulting in greater disc height, but there was no significant difference in L5-S1 segmental lordosis.